El uso de criptomonedas en crowdfunding y en otras estrategías de negocio para promover el crecimiento empresarial internacionalmente - Berdejo, Pedro R. (2019)
This paper analyzes some of the main advantages and opportunities for improvement posed by the use of cryptocurrencies in crowdfunding and other business strategies in a firm or company holding in order to promote its growth internationally. It places specific attention to the advantages of using cryptocurrencies to finance projects through initial coin offerings, for both issuers and investors. Attention is also placed on the regulatory improvement opportunities needed for both protecting them, but especially the latter, from scams, and consolidating full acceptance of this financing option in the international business community.